LITERATURE REVIEW: ANALISIS PENGENDALIAN INTERNAL DAN UPAYA PENCEGAHAN KECURANGAN AKUNTANSI SEKTOR PUBLIK - Wijayanti, Rahma Putri; Setyawan, Supanji (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
The purpose of writing this article is to analyze internal control as an effort to prevent accounting fraud in the public sector. Literature review method with descriptive qualitative approach is the method applied in this research. The results of the review of these 13 articles show that internal control is an effective effort in preventing accounting fraud in public sector organizations. Having good internal controls will reduce the tendency of accounting fraud in the public sector. Therefore, public sector organizations are expected to implement an effective internal control system in order to minimize the occurrence of accounting fraud.